1985
DOI: 10.1111/j.1471-6402.1985.tb00858.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Psychology of Women Textbooks: Focus on the Afro-American Woman

Abstract: A review was conducted of 28 psychology of women textbooks selected from university libraries and utilizing a psychological approach. The question of whether authors of psychology of women books in their treatment of Afro‐American women had replicated the errors of authors of introductory psychology books in their treatment of women was raised. Of the 28 books reviewed, 18 offered either token or no references to Afro‐American women. It is concluded that race and class biases underlie the exclusion, limited in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 1 publication
1
18
0
Order By: Relevance
“…The current study found that images of women and people of color support a narrow or stereotypical view of these groups, which is similar to prior research (Allen & Wallace, 2010;Baro & Eigenberg, 1993;Clawson & Kegler, 2000;Curry, 2001;Dorworth & Henry, 1992;Eigenberg & Baro, 1994;Ferree & Hall, 1990;Greene, Gabbidon, & Ebersole, 2001;Low & Sherrard, 1999). And, the overwhelming absence of images of women of color is consistent with studies that have looked at this issue specifically (Brown et al, 1985;Curry, 2001;Eigenberg & Baro, 1994;Ferree & Hall, 1990;Hogben & Waterman, 1997). In general, this study confirmed that women and people of color are underrepresented in terms of total individuals and that how they are portrayed continues to reinforce traditional views about race and gender.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current study found that images of women and people of color support a narrow or stereotypical view of these groups, which is similar to prior research (Allen & Wallace, 2010;Baro & Eigenberg, 1993;Clawson & Kegler, 2000;Curry, 2001;Dorworth & Henry, 1992;Eigenberg & Baro, 1994;Ferree & Hall, 1990;Greene, Gabbidon, & Ebersole, 2001;Low & Sherrard, 1999). And, the overwhelming absence of images of women of color is consistent with studies that have looked at this issue specifically (Brown et al, 1985;Curry, 2001;Eigenberg & Baro, 1994;Ferree & Hall, 1990;Hogben & Waterman, 1997). In general, this study confirmed that women and people of color are underrepresented in terms of total individuals and that how they are portrayed continues to reinforce traditional views about race and gender.…”
Section: Discussionsupporting
confidence: 91%
“…The absence of women of color was also specifically noted in another study that analyzed psychology of women textbooks. This study found that African American women generally were absent or discussed in a token fashion compared to White women (Brown et al, 1985).…”
Section: Literature Reviewmentioning
confidence: 93%
“…Implications of incorporating the contents for other courses in the psychology curriculum are discussed.Eighteen of the 28 textbooks on the psychology of women reviewed by Brown, Goodwin, Hall, and Jackson-Lowman (1985) contained few or no references to Afro-American women. W e offer a possible structure for including this content by organizing the course discussions around major themes.…”
mentioning
confidence: 99%
“…Eighteen of the 28 textbooks on the psychology of women reviewed by Brown, Goodwin, Hall, and Jackson-Lowman (1985) contained few or no references to Afro-American women. Asian.…”
mentioning
confidence: 99%
“…Many of these, however, have essentially defined women's experience as that of white, middle-class North American women (Brown et al 1985). There has been a noticeable improvement in the representation of racial and ethnic minority groups, as well as of women, though substantial efforts are still needed.…”
mentioning
confidence: 99%